Uso da espectroscopia Vis/Nir na discriminação de folhas de Castanheira-do-Pará (Bertholletia excelsa Bonpl.) na terra indígena Xipaya - OLIVEIRA, Kananda Maria Moraes (2019)
The Castanheira-do-Pará (Berthollettia excelsa Bonpl.) with a great social, economic and ecological value, your 29 almond sets up as one of the most important products to forest economy and one of the main source of income on 30 riverside and indigenous community of amazon. The increase of exploitation on the native chestnuts of Brazilian 31 amazon, has contributed to the decrease of castanha-do-pará’s almond production. However, this study aims verify 32 the VIS/NIR spectroscopy use to discriminate the castanheira-do-pará’s leaves natives from twp indigenous 33 communities. This study was conducted on those two indigenous village: Tukamã and Tukayá on Xipaya’s 34 indigenous land, Altamira, Pará’s state. Initially, were collected leaves samples of 30 chestnut trees, being 15 of 35 each community. After, those samples were sent to Laboratório de Anatomia e Qualidade da Madeira (Wood’s 36 anatomy and quality lab) from Paraná University (UFPR). It was utilized CIELAB system to determine color, 37 realizing 10 measurement randomly in the visible spectrum area, the variables (L*, a*, b*, C, e h*), were analyzed 38 within normality by the Kolmogorov-Smirnov (K-S) test, by probability of 95%, as precedence, the comparison 39 between averages were realized through the Tukey’s test, using 95% as probability. The NIR’s spectrum were 40 obtained through the Tensor 37 spectrometer, on each of 30 leaves of chestnuts from both precedencies. On the 41 samples differentiation, were utilized the Principal Components Analysis (PCA) in harmony with the second 42 derivate, and the Unscrambler X (version 10.1) software. With the results, it may concluded that the average 43 spectrum from NIR and PCA altogether with the second derivate showed most promising on discriminating the 44 leaves of chestnut on both communities. 45 Keywords: Colorimetric parameters; spectral curve; TI Xypaya.